2017
DOI: 10.1140/epjst/e2016-60391-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of extreme intensity pulses in optically injected semiconductor lasers

Abstract: The predictability of extreme intensity pulses emitted by an optically injected semiconductor laser is studied numerically, by using a well-known rate equation model. We show that symbolic ordinal time-series analysis allows to identify the patterns of intensity oscillations that are likely to occur before an extreme pulse. The method also gives information about patterns which are unlikely to occur before an extreme pulse. The specific patterns identified capture the topology of the underlying chaotic attract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In semiconductor lasers, the first experimental demonstration of giant pulses was released in 2011 [105] and the rare occurrence of these high-amplitude pulses was confirmed by simulations based on a simple noise-free rate equation model compatible with a deterministic non-linear process. Most of the experimental and numerical works studying giant pulses in semiconductor lasers focus on an injection scheme [106][107][108]. VCSELs and laser diodes are the most common devices in these experiments because they are renowned for their sensitivity to external perturbations.…”
Section: Giant Pulses In Opticsmentioning
confidence: 99%
“…In semiconductor lasers, the first experimental demonstration of giant pulses was released in 2011 [105] and the rare occurrence of these high-amplitude pulses was confirmed by simulations based on a simple noise-free rate equation model compatible with a deterministic non-linear process. Most of the experimental and numerical works studying giant pulses in semiconductor lasers focus on an injection scheme [106][107][108]. VCSELs and laser diodes are the most common devices in these experiments because they are renowned for their sensitivity to external perturbations.…”
Section: Giant Pulses In Opticsmentioning
confidence: 99%
“…Actually, it has been previously shown that hierarchies and probabilities of the ordinal patterns offer a better characterization of the dynamical regimes of some complex systems, identifying transitions and behaviors that are not detected by more traditional statistical tools [31][32][33][34]. Ordinal patterns analysis can also be helpful to forecast extreme events in complex dynamics such as those obtained from an optically injected semiconductor laser [35], a semiconductor laser with optical feedback in the low frequency fluctuations regime [36], and a Raman fiber laser in the chaotic regime [37]. Besides, it is worth highlighting that the predictive capability achieved with ordinal patterns can go beyond the one reached by more conventional tools as it has been very recently shown for the complex dynamics of the paradigmatic Duffing oscillator [30].…”
Section: An Ordinal-patterns-based New Approach To Time-delay Identificationmentioning
confidence: 99%
“…Most of the experiments and numerical works studying extreme events in semiconductor lasers focus on an optical injection scheme. 18,[34][35][36][37][38][39] VCSELs and laser diodes are the most common devices in these experiments because they are renowned for their sensitivity to perturbations leading to nonlinear phenomena. A very limited number of papers deal with the study of extreme events in the case of OF, 16,40,41 and, among these papers, conventional OF is sometimes replaced by phase-conjugate feedback 15,42 or filtered OF.…”
Section: Introductionmentioning
confidence: 99%